Charlotte Lennox : an independent mind - Carlile, Susan, 1967- (University of Toronto Press, 2018)
"Charlotte Lennox (c. 1729-1804) was an eighteenth-century English novelist whose most celebrated work, The Female Quixote (1752), is just one of eighteen works spanning a forty-three year career. Susan Carlile's critical biography of Lennox focuses on her role as the central figure in the professionalization of authorship in England. Lennox engaged in the most important literary and social discussions of her time, including the institutionalizing of Shakespeare as national poet, the career of playwriting for women, and the role of magazines as instructive texts for an increasingly literate population. Her stories of independent women influenced Jane Austen, especially in her novels Northanger Abbey and Sense and Sensibility. Carlile's work is the first biographical treatment of Lennox to include the new cache of correspondence that was released in the early 1970s and reveals her pioneering roles in making Greek drama accessible and in serializing novels in magazines. Carlile places Lennox in the context of intellectual and cultural history and reveals how she was part of an ambitious, progressive literary and social movement."-- Provided by publisher
Keywords: Lennox, Charlotte, -- approximately 1729-1804.; Lennox, Charlotte, -- approximately 1729-1804; Women authors, English -- Biography.; Novelists, English -- 18th century -- Biography.; Écrivaines anglaises -- Biographies.; Romanciers anglais -- 18e siècle -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Women authors, English; Novelists, English; Biography; Biographies; Biographies.